2009
DOI: 10.1089/ten.tea.2008.0501
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast and Osteoclast Differentiation in anIn VitroThree-Dimensional Model of Bone

Abstract: There is increasing interest in developing new in vitro tissue models using typical tissue engineering approaches. This study was designed to (1) develop a novel three-dimensional (3D) in vitro model of bone by seeding murine primary osteoblasts and osteoclast precursors on a resorbable porous ceramic scaffold based on silicon-stabilized tricalcium phosphate (Skelite), and (2) investigate bone cell interactions in a 3D environment mimicking an in vivo condition and compare it to traditional two-dimensional (2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…Some authors report on successful cultures of osteoblast cell lines or primary osteoblasts in combination with PBMC or isolated monocytes. The cells were of murine or human origin and were cultivated with or without the addition of M-CSF and RANKL (Bloemen et al, 2009;Greiner et al, 2009;Jones et al, 2009;Tortelli et al, 2009;Bernhardt et al, 2010). Only few publications dealing with co-cultures based on BMSC are known.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors report on successful cultures of osteoblast cell lines or primary osteoblasts in combination with PBMC or isolated monocytes. The cells were of murine or human origin and were cultivated with or without the addition of M-CSF and RANKL (Bloemen et al, 2009;Greiner et al, 2009;Jones et al, 2009;Tortelli et al, 2009;Bernhardt et al, 2010). Only few publications dealing with co-cultures based on BMSC are known.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblasts also regulate the growth of osteoclasts by secreting OPG, a decoy receptor for RANKL and therefore a competitor of RANK, to restrain the activity of the RANKL-RANK system [4]. Thus, the ratio of RANKL to OPG dictate the activity of osteoclasts, the resorption of bone [1,24]. Along this line, a recent study demonstrated that knockdown of hRpn13 expression decreased the total number of osteoclasts [18].…”
Section: Discussionmentioning
confidence: 99%
“…Adult bone is renewed and remodeled through coordinated processes regulated by osteoblasts and osteoclasts [24], which are in turn mediated by the ubiquitin-proteasome system. Osteoclasts resorb bones, whereas osteoblasts form new bones at the same site.…”
Section: Introductionmentioning
confidence: 99%
“…However these authors also report a discontinuity of the resorption pattern, which might be caused by the complex three-dimensional structure of the material. The differentiation of murine osteoclast precursors in a porous silicon-stabilized ceramic was investigated by Tortelli et al in co-culture using murine osteoblasts (Tortelli et al, 2009). Gene expression of osteoclastic markers TRAP and cathepsin K was lower for cells cultured in the porous ceramic compared to the control on polystyrene surfaces.…”
Section: Discussionmentioning
confidence: 99%